All-Quartz High Accuracy MEMS Pressure Sensor Based on Double-Ended Tuning Fork Resonator. (2015) - Wang, J.; Zhao, C.; Zhao, G.H.; Jin, X.F.; Zhang, S.M.; Zou, J.B.
Abstract: This paper reports an all-quartz high accuracy MEMS absolute pressure sensor based on high Q double-ended tuning fork (DETF) resonator, which is suitable for application in automotive, petroleum, meteorological, aerospace and spacecraft field. etc. The main parts of the MEMS pressure sensor, including the DETF resonator, diaphragm and back cavity structure, are all fabricated by quartz crystal using MEMS process. These pieces are bonded together as 'sandwich' structure to form the absolute pressure sensing unit using glass paste under low temperature and vacuum condition. This process could effectively eliminate the thermal stress effect and form the reference vacuum cavity. The experimental results show that the quality factor of the DETF resonator is up to 61000, the sensitivity is up to 7.35 Hz/kPa in the operating range 0∼250 kPa, the pressure error is only 0.021%FS over the temperature range -40̊C∼+60̊C.